Java Language Features With Modules, Streams, Threads, I/O, and Lambda Expressions - Sharan, Kishori (Apress, 2018)
Work with essential and advanced features of the Java programming language such as Java modules development, lambda expressions (closures), inner classes, threads, I/O, Collections, garbage collection, and more. Author Kishori Sharan provides over 50 diagrams and 290 complete programs to help you visualize and better understand the topics covered in this book. Java Language Features, Second Edition starts with a series of chapters on the essential language features provided by Java, including annotations, reflection, and generics. These topics are then complemented by details of how to use lambda expressions, allowing you to build powerful and efficient Java programs. The chapter on threads follows this up and discusses everything from the very basic concepts of a thread to the most advanced topics such as synchronizers, the fork/join framework, and atomic variables. This book contains unmatched coverage of Java MIO, the Stream API, the Path API, the FileVisitor API, the watch service, and asynchronous file I/O. With this in-depth knowledge, your data- and file-management programs will be able to take advantage of every feature of Java's powerful I/O framework and much more. You will: Use essential and advanced features of the Java language Code Java annotations and inner classes Work with reflection, generics, and threads Take advantage of the garbage collector Manage streams with the Stream API.